Penguatan Keterampilan Riset dan Penulisan Tugas Akhir Mahasiswa Fisika Universitas Jambi - Anggraini, Rista; Lucky Zaehir Maulana; Yoza Fendriani; Samsidar; Husnul Hamdi; Frastica Deswardani; Febri Berthalita Pujaningsih; Jesi Pebralia; Alrizal; M. Ficky Afrianto; Ichy Lucya Resta (Jurusan Ilmu Sosial dan Ilmu Politik, 2026)
The completion of a final project is an essential component of higher education and often presents significant challenges for students, including those in the Physics Study Program at Universitas Jambi. Various obstacles, such as difficulties in selecting research topics, formulating research problems, designing research methodologies, and producing academic writing in accordance with scientific standards, may hinder the timely completion of studies. Therefore, this community service activity aimed to enhance students' understanding of research skills and final project writing through a webinar on research and scientific writing enhancement. The activity was conducted online via Zoom Meeting on November 20, 2025, involving students from the Physics Study Program of Universitas Jambi. The methods employed included training and academic assistance through lectures, discussions, and interactive question-and-answer sessions. The effectiveness of the activity was evaluated using pre- and post-webinar questionnaires. The results indicated an improvement in participants' understanding across all assessed aspects. The average percentage of participants categorized as not understanding and having low understanding decreased from 10.92% and 45.22% to 0.92% and 14.44%, respectively. In contrast, the average percentage of participants categorized as moderately understanding and highly understanding increased from 34.78% and 8.54% to 49.32% and 37.16%, respectively. These findings demonstrate that the webinar effectively improved students' understanding of final project preparation. Similar activities should be conducted continuously to support the improvement of scientific writing quality and the timely completion of students' studies.